Alternatives to air-conditioning: policies, design, technologies, behaviours. Issue 1 (21st June 2022) - Ford, Brian; Mumovic, Dejan; Rawal, Rajan
Highlights Far from being a panacea, air-conditioning is shown to create social, environmental and economic problems. Alternatives to air-conditioning are identified as a key means of reducing energy demand and carbon emissions, improving resilience to heat, and providing a healthy indoor environment. These alternatives are more than a technological issue and help to reframe coolth as an attribute and not a commodity. This editorial introduces the themes and individual papers in this special issue. It explores the implications of these alternative solutions across a range of issues: health and wellbeing; air quality; heat stress; technical/design solutions; economics and equity; climate change; social expectations and practices; policy and regulation; supply chain and procurement; education and training. Recommendations for change involve policy and regulation, construction industry business models, redefining the design decision process, improving performance and feedback, and updating workforce skills and capabilities.